Comparative account of water chemistry of three perennial rivers of Morang district, Province No. 1, Nepal - Subba, B. R.; Balmiki, N.; Yadav, P. K. (Nepalese Journal of Biosciences, 2016)
A comparative study of water chemistry of Keshaliya, Shinghiya and Lohandra rivers of Province No 1, Morang District, Nepal was performed for one spring season in 2016. Altogether 18 physico-chemical parameters were selected to be determined for each river during spring season. The values of each parameter recorded for the above rivers were pH (6.59 to 8.08), temperature (22.4 to 30.30C), electrical conductivity (336 to 537 NTU), DO (4.17 to 10.65 mg/l), total dissolved solids (168 to 268.5 mg/l), total hardness (145 to 204 mg/l), calcium hardness (106 to 180 mg/l), total alkalinity (172 to 226 mg/l), Silica (180 to 393 mg/l), total nitrogen (4.2 to 14 mg/l) total phosphorous (0.07 to 0.45 mg/l), BOD (4.24 to 126.27 mg/l), COD (9.20 to 252 mg/l), nitrate (<0.05 to 0.18 mg/l), chloride (4 to 36 mg/l), magnesium (4.13 to 21.4 mg/l) and calcium (12.15 to 72.29 mg/l).